Evidence for linguistic deficit in nonlexical processing in reading. A study of a spanish-speaking patient - Martín Plasencia, Pilar; Iglesias Dorado, Jaime; Serrano, Juan Manuel (The Spanish Journal of Psychology, 2008)
Previous studies have shown that in the so-called opaque languages (those in which spelling does not correspond to pronunciation), there are relatively independent routes for lexical and nonlexical processing, that is, for words and nonwords, both in spoken and in written language. On the other hand, in the so-called transparent languages (those in which pronunciation corresponds to written forms), empirical evidence is scarcer. In this study of a neurological patient (parieto-temporal lesion), speaker of a transparent language (Spanish) showing a specific deficit in nonlexical reading processing, linguistic analysis for words was relatively preserved. This finding suggests the use of various routes in the processing of transparent languages.